2020
DOI: 10.1038/s42004-020-0307-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing scandium and yttrium coordination chemistry to advance theranostic radiopharmaceuticals

Abstract: The octadentate siderophore analog 3,4,3-LI(1,2-HOPO), denoted 343-HOPO hereafter, is known to have high affinity for both trivalent and tetravalent lanthanide and actinide cations. Here we extend its coordination chemistry to the rare-earth cations Sc 3+ and Y 3+ and characterize fundamental metal-chelator binding interactions in solution via UV-Vis spectrophotometry, nuclear magnetic resonance spectroscopy, and spectrofluorimetric metalcompetition titrations, as well as in the solid-state via single crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…Thus, the positron emitter 86 Y has been attracting attention over the last few years as a candidate for the design of radiopharmaceuticals for positron emission tomography (PET) due to its versatile half-life (14.74 h) and its well-known chelation chemistry. Moreover, the existence of the β – emitter isotope [ 90 Y]-yttrium allows for the design of theranostic agents, making yttrium an extremely interesting option in nuclear medicine. , To construct a metal-based radiopharmaceutical, a bifunctional chelator is typically chosen, which is basically a chelating ligand provided with a linker capable of conjugation to a targeting vector. , It must be noted that time is of the essence when working with decaying nuclides, so even though kinetic inertness with respect to dissociation is still fundamental, matching the kinetics of formation with the lifetime of the radioisotope is of paramount importance as well. , …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the positron emitter 86 Y has been attracting attention over the last few years as a candidate for the design of radiopharmaceuticals for positron emission tomography (PET) due to its versatile half-life (14.74 h) and its well-known chelation chemistry. Moreover, the existence of the β – emitter isotope [ 90 Y]-yttrium allows for the design of theranostic agents, making yttrium an extremely interesting option in nuclear medicine. , To construct a metal-based radiopharmaceutical, a bifunctional chelator is typically chosen, which is basically a chelating ligand provided with a linker capable of conjugation to a targeting vector. , It must be noted that time is of the essence when working with decaying nuclides, so even though kinetic inertness with respect to dissociation is still fundamental, matching the kinetics of formation with the lifetime of the radioisotope is of paramount importance as well. , …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the widely studied compound L27 continues to be evaluated as a chelating agent towards different metal ions and quite recently its binding interaction with rare earths (Sc 3+ (log β ScL = 25.16), Y 3+ (log β YL = 20.76)) [ 84 ], Hf 4+ and Zr 4+ (log β ML > 42, complexes stable between pH 10 and 10 M HCl) [ 85 ], as well as a coordination study (X-ray absorption spectroscopy—XAS, luminescence measurements) with the heaviest element (einsteinium) that can be generated in quantities that enable classical macroscale studies have been performed [ 86 ]. Complexation studies of L28 with Eu 3+ , Zr 4+ and Th 4+ (log β EuL = 29.65, log β ZrL = 57.26 and log β ThL = 47.71) [ 87 ] evidenced the excellent chelating ability of this compound for both trivalent and tetravalent metal ions at the physiological pH.…”
Section: Poly-hydroxypyridinonesmentioning
confidence: 99%
“…Recently, Abergel s group used various methods to study the coordination chemistry of 3,4,3-LI(1,2-HOPO) with rare earth cations Sc 3+ and Y 3+ . Their results showed that the binding of Sc 3+ and Y 3+ to 3,4,3-LI(1,2-HOPO) is strong, with high thermodynamic stability and rapid radiolabeling at room temperature, indicating that 3,4,3-LI(1,2-HOPO) may be a promising chelating agent of these two metals for in vivo diagnosis and treat-ment [72]. They also synthesized the octa-dentate ligands 3,4,3-LI(1,2-HOPO) 2 (CAM) 2 and 3,4,3-LI(CAM) 2 (1,2-HOPO) 2 , and studied their thermodynamic and photophysical properties with Eu 3+ and Tb 3+ .…”
Section: Multidentate Hydroxypyridinonesmentioning
confidence: 99%